ダイ21ジ ナンキョク チイキ カンソクタイ ナツタイ (1979-1980) ホウコク - 木崎, 甲子郎; キザキ, コウシロウ; Kizaki, Koshiro (1981)
P(論文) 第21次南極地域観測隊の夏期行動の概要を述べる。砕氷艦「ふじ」は約500トンの物資とヘリコプター3機, セスナ・ピラタスポーターの2機を積んで, 1979年11月21日東京港を出帆した。観測隊長木崎以下43名, うち川口越冬隊長以下越冬隊33名である。加うるに, ノルエー極地研究所の太田昌秀博士が交換科学者として参加した。1979年12月12日フリマントル出港, 昭和基地西北西21マイルの氷縁に達したのは12月31日であった。それからヘリコプター輸送が開始され, 翌年2月9日に終了した。その間建設が行われ, とくに夏期隊員宿舎と60klタンクが完成した。2月1日第21次越冬隊が成立した。艦上の定常観測はおおむね例年通りであったが, 氷海や海氷中の微細藻類の研究も行われた。また, やまと山脈やプリンスオラフ海岸の地学調査や測地作業も実施した。また, みずほ基地への人員交替や物資の輸送も行った。1月28日「ふじ」乗組員が事故で重傷を負ったため, 緊急に反転北上することになり, 2月9日ケープタウンに向かって出発した。その途中, マラジョージナヤ基地に立寄り, アメリカ海軍が空輸してくれた酸素ボンベを受領し, ケープタウンには2月21日入港した。患者を下し, ポートルイス, シンガポールを経て1980年4月19日東京港に帰着した。 Summer operations of the 21st Japanese Antarctic Research Expedition (JARE-21) are outlined. The icebreaker FUJI, carrying 500 tons of cargo and equipped with three helicopters and two aeroplanes, Cessna F185 and Piratus Porter, left Tokyo on November 21,1979. The expedition led by Prof. K. KIZAKI consisted of 43 members, 33 of which are of the wintering party led by Prof. S. KAWAGUCHI, deputy leader of the expedition. In addition, Dr. Yoshihide OHTA, geologist of Norsk Polarinstitutt joined the summer party as an exchange scientist. After leaving Fremantle on December 12,1979,the ship reached the edge of fast ice, 21 nautical miles WNW of Syowa Station on December 31,1979. Then, all of the cargo for the wintering party were delivered by helicopters until February 9,1980,while the construction work was carried out, completing the living hut for summer operation and 60 kl fuel tank. On February 1,1980 the wintering members of JARE-21 took over the duties at the station. Scientific programs on boad the FUJI were largely the continuation from previous years : Oceanographic and biological observations and the measurement of HF radio wave intensities were carried out throughout the voyage, and also marine biological studies of micro-algae were conducted within the pack ice area as well as in the sea ice. Several field parties were sent to the Yamato Mts. 300km inland and exposed rocks of the Prince Olav Coast to make geological and geodetic ...